1997
DOI: 10.1002/(sici)1097-4547(19970815)49:4<485::aid-jnr9>3.3.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Factors that contribute to the transneuronal spread of herpes simplex virus

Abstract: In viral encephalitis and retinal necrosis, different herpes simplex virus (HSV) strains spread between neurons in the central nervous system (CNS) by distinctly different routes. The steps of viral infection and spread in a single neuron type and nearby glial cells in vivo have been determined for three different strains of HSV (F, H129, and McIntyre-B). The corneas of mice were inoculated with equivalent titers of the strains. Two to 5 days later, the animals were killed. The spread of viral proteins within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 0 publications
2
28
3
Order By: Relevance
“…Thus, there is uncertainty regarding the direction of transport of the observed viral particles. However, contrary to findings in previous studies (21)(22)(23)(31)(32)(33)(34), we observed enveloped HSV-1 virions within vesicles in axons and growth cones, which could not be derived from entry events as could naked capsids during retrograde transport. Thus, the observation itself is of sufficient validity to support the notion that intraaxonal anterograde transport of both PrV and HSV-1 involves enveloped virions within vesicles.…”
Section: Downloaded Fromcontrasting
confidence: 99%
See 1 more Smart Citation
“…Thus, there is uncertainty regarding the direction of transport of the observed viral particles. However, contrary to findings in previous studies (21)(22)(23)(31)(32)(33)(34), we observed enveloped HSV-1 virions within vesicles in axons and growth cones, which could not be derived from entry events as could naked capsids during retrograde transport. Thus, the observation itself is of sufficient validity to support the notion that intraaxonal anterograde transport of both PrV and HSV-1 involves enveloped virions within vesicles.…”
Section: Downloaded Fromcontrasting
confidence: 99%
“…Besides evidence for separate transport of viral nucleocapsids and envelope components (23,34,37,38), enveloped capsids in vesicles (7,23,27) and sometimes both enveloped and naked nucleocapsids were detected (17,20,36). Recent live-cell imaging studies on transport of fluorescently labeled HSV-1 components provided evidence for cotransport of capsid and envelope components in congruence with the married model (2).…”
mentioning
confidence: 92%
“…Gene knockout studies have demonstrated that PTHrP and Indian hedgehog (Ihh) repress terminal chondrocyte differentiation in avian and murine models (Lanske et al, , 1999Vortkamp et al, 1996;La Vail et al, 1997;Lanske and Kronenberg, 1998). The data suggest that proliferating chondrocytes express PTHrP receptors and Ihh protein as they begin to differentiate.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that in the latent phase the viruses are localized in the neurons of sensory ganglia, but rarely in SGCs [96]. However, SGCs may still have a role in this disease, as they are likely to form a barrier to the spread of the virus between infected and non-infected neurons [91,184]. It can be proposed that a breakdown of this barrier can lead to widespread infection of the ganglia.…”
Section: Sgcs and Herpesmentioning
confidence: 99%